2018
DOI: 10.1177/1073858418760481
|View full text |Cite
|
Sign up to set email alerts
|

Neural Mechanisms of Inflammation-Induced Fever

Abstract: Fever is a common symptom of infectious and inflammatory disease. It is well-established that prostaglandin E2 is the final mediator of fever, which by binding to its EP3 receptor subtype in the preoptic hypothalamus initiates thermogenesis. Here, we review the different hypotheses on how the presence of peripherally released pyrogenic substances can be signaled to the brain to elicit fever. We conclude that there is unequivocal evidence for a humoral signaling pathway by which proinflammatory cytokines, throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(88 citation statements)
references
References 172 publications
(242 reference statements)
2
85
0
1
Order By: Relevance
“…Mutations in the genes encoding pyrin are associated with the distinct interleukin-1β (IL-1β)-mediated autoinflammatory conditions of FMF (16). IL-1β is likely to be the main cause of fever, but attention should be paid to coexisting conditions, such as microsomal prostaglandin E synthase-1 (17). It is reported that the febrile response to lipopolysaccharide-induced IL-1β was lost in chimeric mice that only expressed the microsomal prostaglandin E synthase-1 in hematopoietic cells (18).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the genes encoding pyrin are associated with the distinct interleukin-1β (IL-1β)-mediated autoinflammatory conditions of FMF (16). IL-1β is likely to be the main cause of fever, but attention should be paid to coexisting conditions, such as microsomal prostaglandin E synthase-1 (17). It is reported that the febrile response to lipopolysaccharide-induced IL-1β was lost in chimeric mice that only expressed the microsomal prostaglandin E synthase-1 in hematopoietic cells (18).…”
Section: Discussionmentioning
confidence: 99%
“…DNA between two lox sites aligned in the same direction is excised, while DNA between two lox sites facing each other is inverted by Cre (Branda et al 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Fever is a common symptom of infectious and inflammatory disease. It is well-established that prostaglandin E2 is the final mediator of fever, which by binding to its EP3 receptor subtype in the preoptic hypothalamus initiates thermogenesis (32).The GO enrichment and KEGG enrichment analysis result showed that CR relieved Zika fever and condition deterioration by regulating the expression of PTGS2 and PTGS1 to further inhibit PG release and regulate metabolism to reduce inflammation response.…”
Section: Go Enrichment and Kegg Enrichment Analysismentioning
confidence: 97%